Use of Macrolides in Pregnancy and Lactation According to Evidence-Based Medicine: Pro et Contra - A. A. Khryanin; O. V. Reshetnikov (Антибиотики и Химиотерапия, 2020)
The use of macrolides in the treatment of chlamydial infection during pregnancy and breast feeding is reviewed from the viewpoint of evidence-based medicine. The clinical experience and research data suggest azithromycin to be safe and effective in the obstetric practice.